1997
DOI: 10.1104/pp.115.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Purification and in Vitro Chaperone Activity of a Class I Small Heat-Shock Protein Abundant in Recalcitrant Chestnut Seeds

Abstract: A 20-kD protein has been purified from cotyledons of recalcitrant (desiccation-sensitive) chestnut (Castanea sativa) seeds, where it accumulates at levels comparable to those of major seed storage proteins. This protein, termed Cs smHSP 1, forms homododecameric complexes under nondenaturing conditions and appears to be homologous to cytosolic class I small heat-shock proteins (smHSPs) from plant sources. In vitro evidence has been obtained that the isolated protein can function as a molecular chaperone: it inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 29 publications
1
33
0
1
Order By: Relevance
“…CsHSP17.5, a major sHSP in chestnut trees, was overexpressed in hybrid poplar under the control of an enhanced CaMV 35S promoter. CsHSP17.5 exhibited several interesting features a priori, including the ability to improve cell viability under thermal stress in recombinant bacteria and the outstanding levels it normally reaches in chestnut stems and seeds (Collada et al, 1997;Soto et al, 1999;Lopez-Matas et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CsHSP17.5, a major sHSP in chestnut trees, was overexpressed in hybrid poplar under the control of an enhanced CaMV 35S promoter. CsHSP17.5 exhibited several interesting features a priori, including the ability to improve cell viability under thermal stress in recombinant bacteria and the outstanding levels it normally reaches in chestnut stems and seeds (Collada et al, 1997;Soto et al, 1999;Lopez-Matas et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Third, it significantly improves Escherichia coli viability under heat stress conditions. Fourth, it accumulates at unusually high levels in both stems and seeds, where it reaches levels comparable to those of major storage proteins (Collada et al, 1997;Soto et al, 1999;Lopez-Matas et al, 2004). Besides suggesting a relevant role in thermotolerance, these features indicate that CsHSP17.5 can accumulate in vivo for long periods of time.…”
mentioning
confidence: 91%
“…(Green et al, 2013). The effect of this practice is not only to promote seed hydration but also to enhance the biosynthesis of stressresponse substances, like heat-shock proteins, which can play a role in the fast removal of inhibitors of seed germination (Collada et al, 1997;Bailly, 2004;Berjak and Pammenter, 2008). However, the right combination between treatment temperature, time and optimum temperature for germination, in the case of J. curcas, should be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In woody plants such role was first demonstrated for a purified Castanea sativa (European chestnut) sHSP by Collada et al (1997). Afterwards, Soto et al (1999) found that overexpression of a chestnut protein in bacterial cells enhanced their tolerance to both high and low temperatures.…”
Section: Molecular Chaperones and Stress Tolerancementioning
confidence: 98%